Characterizations of pseudolinear and semistrictly quasilinear functions - IVANOV , Vsevolod I. (Studia Universitatis Babeș-Bolyai Mathematica, 2026)
In this paper, we obtain several new complete characterizations of pseudolinear functions. Two of the results are of first-order and one is derivative free. The results are derived in terms of the Clarke-Rockafellar subdifferential. Additionally, we prove a characterization of the semistrictly quasilinear functions. It is similar to the derivative free characterization of the pseudolinear functions. We also find the conditions such that a semistrictly quasilinear function become pseudolinear. Mathematics Subject Classification (2010): 26B25, 49J52. Received 28 November 2025; Accepted 12 April 2026.